One Lord, One Faith, One Baptism in the Land of ein Volk, ein Reich, ein Führer: The Fifth Baptist World Congress (Berlin, 1934) - McKinney, Blake (Church history, 2018)
The interplay of religion, politics, and state in National Socialist Germany continues to defy facile characterizations. In 1934, mere weeks following the Röhm Putsch in which the Nazi regime committed dozens of political assassinations, Berlin hosted thousands of Baptists from across the globe who would unanimously decry nationalism and racialism and advocate for the separation of church and state. Held from August 4-10, 1934, the fifth Baptist World Congress marks the zenith of German Baptist publicity and international Baptist cooperation during the interwar period. The Congress thus provides a focal point for analyzing interwar British and German Baptist relations. This relationship reflected both international cooperation and the gradual divergence of doctrine along nationalistic lines. German Baptists experienced greater freedom of exercise under the Third Reich than under previous regimes, and they leveraged their international connections in order to further their mission. They refused to become involved in the well-documented Church Struggle of the Confessing Church and the German Christian Movement, and this refusal strained international partnerships. The German Baptist experience challenges many assumptions concerning the churches under the Third Reich as it illustrates the Nazi regime's permissive toleration of a biblicist Free Church group with propagandistically valuable international connections.